Optimization of traffic safety facilities in highway tunnels based on driver’s visual perception - Yunteng Chen; Ling Zhang; Jiexin Zhou (Journal of Intelligent Construction, 2024)
This paper delves into the optimization of traffic safety facilities within highway tunnels by leveraging the inherent visual perception characteristics of drivers. Grounded in the context of Zhejiang Province’s highway construction, the study draws from practical insights provided by highway tunnel projects within the region. Through a meticulous blend of on-site investigations and empirical experimentation, the research assesses the effectiveness of existing safety installations in highway tunnels. The analysis extends to the exploration of optimizing the design and placement of traffic safety facilities, informed by the distinct visual perception tendencies exhibited by drivers. By amalgamating the insights derived from driver perception and real-world highway tunnel dynamics, the paper proposes a refined and contextually attuned approach to enhancing traffic safety measures. This study not only contributes to the field of transportation engineering but also holds the potential to significantly enhance the overall safety of highway tunnel environments.